Integrated conodont biostratigraphy and stable isotope chemostratigraphy from the Tremadocian (Lower Ordovician) of the Yangtze Platform, South China - Yan, Guanzhou; Liu, Jianbo; Lehnert, Oliver; Luan, Xiaocong; Calner, Mikael; Wu, Rongchang (Journal of the Geological Society, 2025)
Tremadocian (Lower Ordovician) carbonate rocks were collected from the Xiangshuidong section in the Hubei Province, South China, and analysed for conodont biostratigraphy. A total of 24 species belonging to 16 genera were recovered from the Nantsinkuan and Fenhsiang formations. Three conodont zones are recognized based on this material: the Rossodus manitouensis Zone, Colaptoconus quadraplicatus–Paltodus pristinus Assemblage Zone and the Paltodus deltifer Zone, in ascending order. A biostratigraphic gap, corresponding to the Cordylodus lindstromi and Cordylodus angulatus zones, implies a major hiatus spanning the Cambrian–Ordovician boundary interval on the Yangtze Platform. A remarkable conodont faunal turnover is evident within the uppermost Rossodus manitouensis Zone and Colaptoconus quadraplicatus–Paltodus pristinus Assemblage Zone, corresponding to the early Tremadocian Base Stairsian Mass Extinction event (BSME). This turnover took place at a stratigraphic interval corresponding to the rising limb of the Top Skullrockian Isotopic Carbon Excursion (TSICE). According to the herein revised conodont biozonation of the Xiangshuidong section, a small but distinct positive shift in (Formula presented.) 238U values begins in the lower part of the Colaptoconus quadraplicatus–Paltodus pristinus Assemblage Zone and contemporaneously with the TSICE. This shift suggests sustained improved oxygenation of the sea-floor environment in the early Tremadocian, post-BSME. There are no apparent (Formula presented.) 238U changes before the BSME.
CRIS-Team Scopus Importer:2025-03-14